APAKAH FAKTOR NILAI PERUSAHAAN, UKURAN KOMITE AUDIT DAN BOARD INDEPENDENCE MEMIIKI PENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR: SUB SEKTOR JASA PERINDUSTRIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hutagaol, Rafael; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (LPPM Universitas Bina Bangsa, 2025)
This research analyzes the influence of audit committee size, institutional ownership, and board independence on firm value. The population used is manufacturing companies in the industrial services sub-sector listed on the Indonesia Stock Exchange during 2021-2023. A total of 10 companies were selected using the purposive sampling method for the research samples. This research uses quantitative methods with secondary data as the main source. Data analysis was carried out using multiple linear regression techniques with the help of SPSS version 25 software. The research results showed that partially, the size of the audit committee, institutional ownership, and board independence affected firm value. Together, these three variables are also proven to influence firm value